2018
DOI: 10.1108/jeim-12-2014-0125
|View full text |Cite
|
Sign up to set email alerts
|

Examining information and communication technology (ICT) adoption in SMEs

Abstract: Purpose Since the 1980s, a substantial number of theories have contributed extensively to information and communication technology (ICT) adoption. Much of such theories regarded ICT adoption as a one-off action as they specifically focus on factors affecting decision making at one decision point. They tend to play down on the fact that as adoption decision progresses through stages, they are supposedly influenced by the same or different factors. Therefore, the purpose of this paper is to examine the dynamic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 64 publications
2
55
0
2
Order By: Relevance
“…With further understanding of the area it became apparent that most reasons were due to self-interest rather than the interest of the business. Examples of which being long term time and cost reduction as suggested in the literature review [6]- [9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With further understanding of the area it became apparent that most reasons were due to self-interest rather than the interest of the business. Examples of which being long term time and cost reduction as suggested in the literature review [6]- [9].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers [6]- [9] argue that after the initial implementation costs, IT is proven to help in both long-term cost reduction and operations' effectiveness. Similarly, Li et al [10] found that introducing new technologies could enable businesses to improve their team building and organisational capability.…”
Section: Benefits For Smes Using Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Múltiples son los beneficios del uso de tecnologías de información (ti) en las organizaciones (Díaz-Pinzón, Gómez-Medina, García-González, Melo-Román, & Sanabria-Villamizar, 2017), así como los factores que afectan el aprovechamiento de estas (Salahshour Rad, Nilashi, & Mohamed-Dahlan, 2017). Particularmente, las mipymes presentan muchos retos en relación con la apropiación de las ti (Afolayan, Plant, White, Jones, & Beynon-Davies, 2015;Eze, 2018). En Colombia, el Ministerio de Tecnologías de la Información y las Comunicaciones (Mintic) ha desarrollado diferentes programas para fomentar el acceso y el uso de tecnologías de la información por parte de las mipymes (Mintic, 2019).…”
Section: Introductionunclassified
“…They typically employ less than 500 workers. They are known for their major advantages including employment creation at low capital cost, flexibility, and innovation [1,59,67]. Economies of most OCED nations comprise nearly 96% to 99% of small and medium enterprises that account for 80% economic growth for those nations.…”
Section: Introductionmentioning
confidence: 99%